Computer experiment in modern geophysics - Бахова, Н.І. (Proceedings of National Aviation University (archive), 2009)
Modern planning methods of computing experiments in geophysics are considered. The factor’s experiment have been given an account in detail. The special attention is given to the experiment tactics and solution adoption.